PENETRATION OF ADENOSINE ANTAGONISTS INTO MOUSE BRAIN AS DETERMINED BY EX VIVO BINDING - Baumgold, Jesse (1992)
The penetration of the adenosine antagonists 8-cyclopentyl-1,3-dimethylxanthine (CPT), 8-cyclopentyl-1,3-dipropylxanthine (CPX), 8(p-sulfophenyltheophylline (8-PST), and 8-[4-[[[[(2-aminoethyl) amino]carbonyl]methyl]oxy]phenyl]-l,3-dipropylxanthine (XAC) into mouse brain was determined using ex vivo binding and locomotor studies. CPT and CPX (25 and 0.25 mg/kg, respectively) both penetrated into brain in substantial amounts: 49 and 17% of theoretical levels assuming free penetration throughout the body, 10 min after i.p. injection, respectively. Brain levels of CPT decreased rapidly, declining to undetectable levels by 30 min post-injection, whereas levels of CPX declined much more slowly. As expected, no detectable brain levels of 8-PST were found following i.p. injection of 50 mg/kg. XAC (20 mg/kg) penetrated into brain poorly: 1.6% after 10 min and 3.2% 20 min post-injection. The ability of CPT to stimulate locomotor activity paralleled the brain levels, i.e. it was similar to theophylline at short times and the effect rapidly diminished. These studies demonstrate the usefulness of ex vivo binding in determining CNS penetration of adenosine receptor ligands.